Ca2+-Calmodulin Modulates Ion Channel Activity in Storage Protein Vacuoles of Barley Aleurone Cells. - Bethke, P. C. (1994)
Many plant ion channels have been identified, but little is known about how these transporters are regulated. We have investigated the regulation of a slow vacuolar (SV) ion channel in the tonoplast of barley aleurone storage protein vacuoles (SPV) using the patch-clamp technique. SPV were isolated from barley aleurone protoplasts incubated with CaCl2 in the presence or absence of gibberellic acid (GA) or abscisic acid (ABA). A slowly activating, voltage-dependent ion channel was identified in the SPV membrane. Mean channel conductance was 26 pS when 100 mM KCl was on both sides of the membrane, and reversal potential measurements indicated that most of the current was carried by K+. Treatment of protoplasts with GA3 increased whole-vacuole current density compared to SPV isolated from ABA- or CaCl2-treated cells. The opening of the SV channel was sensitive to cytosolic free Ca2+ concentration ([Ca2+]i) between 600 nM and 100 [mu]M, with higher [Ca2+]i resulting in a greater probability of channel opening. SV channel activity was reduced greater than 90% by the calmodulin (CaM) inhibitors W7 and trifluoperazine, suggesting that Ca2+ activates endogenous CaM tightly associated with the membrane. Exogenous CaM partially reversed the inhibitory effects of W7 on SV channel opening. CaM also sensitized the SV channel to Ca2+. In the presence of ~3.5 [mu]M CaM, specific current increased by approximately threefold at 2.5 [mu]M Ca2+ and by more than 13-fold at 10 [mu]M Ca2+. Since [Ca2+]i and the level of CaM increase in barley aleurone cells following exposure to GA, we suggest that Ca2+ and CaM act as signal transduction elements mediating hormone-induced changes in ion channel activity.